State anxiety and subjective well-being responses to acute bouts of aerobic exercise in patients with depressive and anxiety disorders. Issue 10 (19th November 2008) - Knapen, J; Sommerijns, E; Vancampfort, D; Sienaert, P; Pieters, G; Haake, P; Probst, M; Peuskens, J
Abstract : Objective: Acute aerobic exercise is associated with a reduction in state anxiety and an improvement in subjective well-being. The objective of the present study was to contrast the effects of aerobic exercise at self-selected intensity versus prescribed intensity on state anxiety and subjective well-being (negative affect, positive well-being and fatigue) in patients with depressive and/or anxiety disorders. In addition, the potential impact of heart rate feedback was assessed. Methods: Nineteen men and 29 women performed three test conditions on a bicycle ergometer during 20 minutes: two tests at self-selected intensity; one with and another without heart rate feedback, and a third test at the prescribed intensity of 50% of the maximal heart rate reserve according to Karvonen. Tests were executed in random order. State anxiety and subjective well-being were evaluated using the state anxiety inventory and the subjective exercise experiences scale. Results: After 20 minutes cycling, patients showed significantly decreased state anxiety and negative affect in the three conditions. The magnitude of the reduction did not differ significantly between the three conditions. Only cycling at self-selected intensity enhanced positive well-being. Cycling at 50% of the maximal heart rate reserve decreased fatigue, whereas cycling at self-selected intensity increased fatigue. Conclusions: The response in state anxiety and negative affect was unaffected by the type of aerobic exercise. Self-selected intensity influenced exercise-induced changes in positive well-being and fatigue in a positive and negative way, respectively.